Assessing the Guidance Need of Secondary Level Students: An Emergence Towards National Education Policy 2020 - Barik, Shibani; Subhrajyoti, Trupti; Acharya, Amulya Kumar (Stallion Journal for Multidisciplinary Associated Research Studies, 2025)
Education is crucial for a successful nation, promoting economic growth, social stability, and individual empowerment. It unlocks potential, helping students understand their strengths, weaknesses, interests, and aspirations through providing appropriate guidance. In the path of becoming 'Vishwaguru,' to achieve educational excellence, the schools must be vigilant about 21st-century learners' diverse needs to prepare them for the global market with proper guidance and counselling because learners aged 13-16 years have been getting overwhelmed for dynamic causes. The present study aims to identify the guidance needs of secondary-level students through a descriptive survey method. Randomly selected 200 samples from different schools of Nilagiri block and Balasore Sadar were administered with a standardized tool developed by P. Sharma & D. Sharma (2020). The study resulted in the finding that around 65% of secondary-level students had an average need for guidance. The majority of secondary-level students (63.31%) need support in social aspects, while a significant 61.26% need guidance on academics, 60.43% need to choose correct vocational paths, and 52.10% need help regarding the solution of personal issues. Moreover, female students, students from rural areas, and, surprisingly, the students of government secondary schools need more serious guidance than their counterparts. The study will be helpful in developing targeted intervention programs to address the specific needs of secondary-level students, particularly in social, educational, vocational, and personal aspects. Additionally, it highlights the importance of providing guidance and support to female students, those in rural areas, and those attending government secondary schools to ensure their overall well-being and success.